Analysis of Corporate Tax Turnover Ratio as an Indicator of Taxpayer Compliance Level - Putra, Rizki Pratama; Santioso, Linda (Quantitative Economics and Management Studies, 2025)
This research focuses on assessing tax potential from the aspect of calculating tax ratios, namely CTTOR, GPM, and NPM as one of the indicator tools to explore taxpayer potential in mapping the risk of non-compliance. This research method uses a descriptive type of research with a quantitative analysis approach. The research technique in data collection uses secondary data, namely audited financial reports obtained from the IDX. The analysis tool uses CTTOR, GPM, and NPM by comparing the tax ratios set from the Directorate General of Taxes. The sample of this study is 3 corporate taxpayers engaged in the animal feed sub-sector. The results of this research show that the average values of CTTOR, GPM, NPM in 2022 are 0.69%, 12.09%, and 2.81% while the DGT benchmark is 2.42%, 16.89%, and 4.78% with a difference of 1.73%, 4.8% and 1.97%. Then the average values of CTTOR, GPM, and NPM in 2023 are 0.71%, 11.99%, and 2.04% with a difference of 1.71%, 4.9% and 2.7% on the DGT benchmark. So it can be concluded from the aspects of CTTOR, GPM, and NPM that the level of corporate tax compliance in the animal feed sub-sector is still below the standards set by the DGT. A significant difference that shows the potential for taxes that have not been explored optimally.